Profiling Skin Microbiome in Healthy Young Adult Representing Javanese, Papuans, and Chinese Descent in Indonesia - Stella Vania; Amarila Malik (Bogor Agricultural University, Indonesia, 2021)
Skin serves as the first physical barrier and biological barrier by the colonization of commensal bacteria to prevent pathogen invasion. It was known that the disruption on normal commensal microbiota composition or dysbiosis causes skin diseases, while the skin microbiota diversity itself is influenced by several factors, one of them is ethnicity. This study shows the influence of ethnicity factor in Papuans, Javanese, and Chinese descent young adults living in Jakarta on skin microbiome profiles. The microbiota genomic DNA are extracted from the face skin samples and sequenced with Next Generation Sequencing method to be further analyzed. The result shows that individuals with the same ethnic background share similar skin microbiome characteristics. The greatest skin microbiome alpha diversity is shown by the Papuans and the Chinese descent the smallest. Ethnicity factor that shows statistically significant differences in interindividual dissimilarities are independent of other intriguing factors such as age, geographical location, etc. Therefore the ethnic origin of individuals especially from three ethnics above is a factor to be considered in skin microbiome research and the skin microbiota composition can be used for potential future applications.